Do intense weather events influence dogs' and cats' behavior? Analysis of owner reported data in Italy - Palestrini, Clara; Minozzi, Giulietta; Mazzola, Silvia Michela; Lopez, Annalaura; Cannas, Simona (Frontiers in Veterinary Science, 2022)
Climate change is a threat to global health and can affect both veterinary and human health. Extreme weather events, including sudden and violent thunderstorms or periods of extreme heat, are predicted to rise in frequency and severity and this could lead owners to significantly change their habits and schedules based on the weather, could modify human management and could aggravate pre-existing behavioral problems in pets. The aims of the present study were to identify and quantify possible extreme weather events impact on management, behavior, and behavioral problems of Italian dogs and cats, based on previous owners’ experiences with their animals. Two questionnaires were prepared, one for dogs and one for cats, investigating owners’ perceptions of the impact of weather events on their pets’ behavior. A number of 392 dogs and 426 cats’ owners answered the questionnaire. Our study showed that many behaviors in both species were equally modified by environmental temperature. Play and activity increased with cold weather and decreased with heat, and sleep increased with drops in temperature and with hot weather. In particular, the increase in activity in correspondence with the thermic drop was more significant in males, while the increase in playing behavior was statistically greater in the Sheepdogs and Cattle dogs –group1. Weather events did not affect aggressive and house soiling behaviors in both dogs and cats, but extreme weather events, including wild thunderstorms, torrential rains, and flooding influenced the pets’ behavior. Understanding how pets modify their behaviors based on a different owners’ schedule and to extreme weather events can help to refine prevention strategies through societal changes and owner education.